A Terahertz Controlled‐NOT Gate Based on Asymmetric Rotation of Polarization in Chiral Metamaterials. Issue 18 (18th July 2017) - Xu, Wei‐Zong; Shi, Ya‐Ting; Ye, Jiandong; Ren, Fang‐Fang; Shadrivov, Ilya V.; Lu, Hai; Liang, Lanju; Hu, Xiaopeng; Jin, Biaobing; Zhang, Rong; Zheng, Youdou; Tan, Hark Hoe; et al.
Abstract : Logical operation based on polarization encoding of light is important for future data transmission and information processing. However, in the terahertz (THz) region, chiral materials with large optical activity are not available in nature, and the effective manipulation of polarization states remains challenging. Here, the authors demonstrate a double‐layer bi‐anisotropic metamaterial that consists of planar spiral and cut‐wire layers separated by a polyimide film. Strong asymmetric polarization rotation of two orthogonal linear polarizations can be observed around 0.53 THz. By investigating the correlation between two linear polarization states before and after the spiral‐wire metamaterial at this frequency, a controlled‐NOT (CNOT) gate operating on two linear‐polarization‐based qubits is further exploited. The processing mechanism of the asymmetric rotation and CNOT gate is attributed to the scattering of dipole momentum based on classical multipole theory. This polarization processor's architecture is promising for robust and energy‐efficient THz polarization control, and also provides an effective path for the development of future optical supercomputing technology. Abstract : A double‐layer bi‐anisotropic metamaterial is demonstrated, which exhibits strong asymmetric polarization rotation of two orthogonal linear polarizations around 0.53 THz. The application of the proposed metamaterial working as a controlled‐NOT gate is further exploited. Such a polarization processor's architecture provides an effective path for the development of terahertz polarization control and future optical supercomputing technology.